Enhancing students' information literacy through project-based learning: A mini research on plant morphology identification - Neni Murniati; Y. Yennita; Dinda Triski Oktaria Ha; R. Riyanto (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Plant morphology courses develop students’ understanding of plant structures and identification skills through mini-research activities. Effective species identification requires a literature review and the ability to find, evaluate, and use relevant information. This qualitative study examines students’ information literacy skills in completing plant identification projects using Project-Based Learning (PjBL). The research involved 63 biology education students enrolled in a plant morphology course. Data were collected through questionnaires assessing information literacy skills and portfolios documenting mini-research reports. Descriptive analysis revealed that the PjBL model enhanced students’ information literacy skills, with 65% classified as "in progress," indicating ongoing development. Students successfully identified various plant types, including ornamental plants, medicinal plants, shade trees, and fruit and vegetable plants. The ability to locate relevant information was a key factor in improving literacy skills. Additionally, collaboration, interest, and the use of technology supported students’ literacy development. These findings suggest that integrating PjBL into plant morphology courses can foster essential information literacy competencies.